The analysis of the collective diet of preschool children in Niš, Serbia and potential health risks - Bonić, Dejan; Stanković, Aleksandra; Krstić, Ivan; Davidović, Dejan; Radojković, Ivan; Veličković, Ana; Veličković, Dragan (Progress in Nutrition, 2018)
Preschool age is an important period for acquiring the eating habits and evaluation of the children’s collective nutrition in kindergartens is especially important for prevention of potential health risks. The aim of the paper was to assess the kindergarten servings in Niš (Serbia), in respect to probable health risks. The study was done in the period from 2011 to 2014. In daily portion, macronutrient shares were determined by using proximate analysis in the accredited laboratory and micronutrient shares were calculated by food composition tables. The mean energy value of the examined servings was (range: 657.7-1,1363 kcal). The share of macronutrients in the total energy intake were in accordance with the national recommendations: protein (13.54%), fat (32.32%) and carbohydrates (54.16%). An average daily serving contained 6.22 mg of Fe, 107 mg of Mg, 2411 mg of Na, and 351.4 mg of Ca. The results of our study indicate that children in kindergartens in Nis, Serbia consumed servings with no risk of developing obesity. The total quality of servings should be improved, because of the observed inadequacies of minerals and vitamins and possible health risks.